Pain Medicine : An Essential Review - Yong, R. Jason; Nguyen, Michael; Nelson, Ehren; Urman, Richard D. (Springer International Publishing : Imprint: Springer, 2017)
This book serves as a practical resource for pain medicine providers. It presents important clinical concepts while covering critical pain medicine fundamentals. Chapters were carefully chosen to cover common aspects of clinical pain medicine and also follow a common format to facilitate quick look-up. Each chapter includes a concise discussion of the latest supporting evidence as well as relevant case scenarios. The coverage is clinically and board relevant, evidence-based and up-to-date. It will appeal to residents preparing for the written board examination and practitioners preparing for board re-certification, which now occurs every 10 years. Beyond these groups, the book has the potential to appeal to learners and practitioners around the world; pain medicine is burgeoning globally, and there is great need for concise, clinically relevant resources. .